EFL Teachers' beliefs and Challenges towards Technology-Integrated Online Classrooms during the Covid-19 Pandemic at Ahram Canadian University - هدي علي علي (Faculty of Education - Port Said University, 2021)
AbstractThe Covid-19 pandemic has offered us a challenging opportunity to pave the way for introducing digital learning. The unexpected shift of teaching the English language from face-to-face classroom to online learning activities through digital platforms has raised significant challenges for English teachers and students. Thus, the current study aims to investigate the EFL teachers' beliefs towards the effectiveness of technology-integrated online classrooms and the challenges they experienced during the Covid-19 pandemic. The study adopts an exploratory sequential design whereby online questionnaire and interviews were used to come up with a comprehensive report on the impact of technology-integrated online classrooms during the Covid-19 pandemic and the EFL teachers' challenges faced in online teaching. For data collection, 48 instructors at the English language department, Ahram Canadian University, participated in the study. Due to the pandemic lockdown, the study took place in the spring semester of the academic year 2020. The current study focused on addressing the following questions: Is technology-integrated online classroom beneficial during the Covid-19 pandemic?